ANALISIS PERANAN BADAN USAHA MILIK DESA (BUM DESA) DALAM PENINGKATAN PENDAPATAN ASLI DESA DI KABUPATEN GOWA - Ashar Prawitno; Rahmatullah Rahmatullah; Safriadi Safriadi (KRITIS : Jurnal Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2019)
One source of Original Local Government (village) Revenue (PADes) that can be managed by the village government is by establishing a village owned enterprises (BUM Desa), which is a village economic institution / body formed and owned by the village government and the community, managed economically independently and professionally.The objectives of this study are: (1) To analyze the factors that play a potential role for BUM Desa in Kabupaten Gowa. (2) To analyze the steps taken by the Regional Government of Gowa Regency in realizing the establishment of BUM Desa. The type of research that will be used is descriptive research type which is a type of research that aims to provide a systematic, factual and accurate description of the data available in the field about the role of Village-Owned Enterprises (BUM Desa) in Gowa Regency. The results of the study are as follows: (a) For the Establishment, the Government of Gowa Regency has made efforts to establish Village Owned Enterprises (BUMDes) in all villages within the scope of Gowa Regency. (b) in supporting the running of the organization, the Government of Gowa Regency has established a Regional Regulation as a guideline for the implementation of village-Owned Enterprises, namely Regency Regulation Gowa No. 7 of 2015 concerning Procedures for Forming and Managing Village-Owned Enterprises. However, human resource problems in managing village-owned enterprises are still slow and tend to decline. Keywords: Pole, village owned enterprises, village